Feeding habits and habitat selectivity of the shortnose guitarfish, Zapteryx brevirostris (Chondrichthyes, Rhinobatidae), off north Argentina and Uruguay - Barbini, Santiago Aldo (2011)
Dietary shifts with predator’s size, maturity stage and season and bottom type selection of Zapteryx brevirostris were evaluated, using generalized linear models. In terms of index of relative importance, the most important prey were amphipods (39.17%), polychaetes (22.33%) and lancelets (20.33%), followed by decapods (8.93%), cumaceans (5.41%) and isopods (3.41%). Z. brevirostris consumed mainly polychaetes and amphipods in spring and summer, ate more cumaceans in winter, consumed more lancelets in spring, and preyed more heavily on decapods and isopods in summer. As Z. brevirostris increased in size, the consumption of decapods, polychaetes and isopods was higher, but the consumption of amphipods decreased. Mature individuals of Z. brevirostris consumed more lancelets than juveniles. Z. brevirostris selected sand over other bottom types. The diet of Z. brevirostris can be influenced by the selectivity of this species for sandy bottoms. As sandy bottoms are exposed to a high intensity of bottom trawling, the positive selection of sandy bottoms increases the vulnerability of Z. brevirostris by exposing it to fishing mortality.